Systematic Functional Testing with Decision Table - Arantes, Gilmar F.; Freitas, Diogo M. de; Leitão-Júnior, Plínio S.; Vincenzi, Auri M. R. (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2016: Anais do I Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2016)
Context. In view of the high impact that the test activity has to the cost of software development and the great popularity of Functional Testing Techniques, it is observed that it is necessary to seek strategies that reduce the cost associated with testing without significant loss of quality. Purpose. To introduce an evolution of the method Functional Systematic Test (TFS), the Functional Test Systematic table-Decision (TFS-TD), and to compare the efficiency and effectiveness of both by using programs that are simple and available on LINUX distributions. Methodology. It is a quantitative, descriptive and case studies research, for the evaluation of TFS and TFS-TD methods and its comparison. Results. Guidelines and an iterative process for the application of TFS-TD were defined. Also, through the case studies, the effectiveness and efficiency of the method was quantified and confronted to the TFS method. Conclusions. The case studies revealed that the TFS-TD presents considerable savings in test cases with minimal loss in quality.